2008
DOI: 10.1080/14768320601124899
|View full text |Cite
|
Sign up to set email alerts
|

Regret associated with the decision for breast reconstruction: The association of negative body image, distress and surgery characteristics with decision regret

Abstract: This study investigated the influence of psychosocial and surgical factors on decision regret among 123 women diagnosed with breast cancer who had undergone immediate (58%) or delayed (42%) breast reconstruction following mastectomy. The majority of participants (52.8%, n = 65) experienced no decision regret, 27.6% experienced mild regret and 19.5% moderate to strong regret. Bivariate analyses indicated that decision regret was associated with negative body image and psychological distress - intrusion and avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 37 publications
4
70
1
Order By: Relevance
“…Psychometric evaluation of the scale has shown high levels of internal consistency (Cronbach α = 0.86), and it has been previously validated in breast cancer and breast reconstruction patients. 11,30,31 …”
Section: Primary Outcomementioning
confidence: 99%
“…Psychometric evaluation of the scale has shown high levels of internal consistency (Cronbach α = 0.86), and it has been previously validated in breast cancer and breast reconstruction patients. 11,30,31 …”
Section: Primary Outcomementioning
confidence: 99%
“…In comparison, there were no differences in the internal reliability consistency or discriminant validity of the DRS among men faced with a prostate treatment decision. Based on the initial validation study, several studies report the DRS as a reliable measure in oncology patients faced with treatment decisions and participation in clinical trials (Sheehan, Sherman, Lam, & Boyages, 2007a; Sheehan, Sherman, Lam, & Boyages, 2007b; Stryker, Wray, Emmons, Winer, & Demetri, 2006; Whalen, Shin, Somerville, & McLean, 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…27 Women who report body image concerns are more likely to experience decisional regret. 26 Other studies have reported no differences in perceived body image between women choosing BR and women who don’t choose BR, 28 or reported mixed psychological outcomes. These studies indicate no differences with regard to some psychological outcomes (e.g., anxiety), but significant differences on other psychological outcomes (e.g., lower depressive symptoms among women undergoing mastectomy without BR as compared to women undergoing mastectomy with BR.…”
Section: Introductionmentioning
confidence: 99%
“…17,2425 About half of women undergoing BR report some decisional regret. 26 Women who have post-operative complications experience elevated anxiety, depression, and cancer-specific distress. 27 Women who report body image concerns are more likely to experience decisional regret.…”
Section: Introductionmentioning
confidence: 99%